Chemotherapy-Induced Sclerosing Cholangitis Caused by Systemic Chemotherapy. Issue 7 (July 2019) - Kusakabe, Akira; Ohkawa, Kazuyoshi; Fukutake, Nobuyasu; Sakakibara, Mitsuru; Imai, Toshihiro; Abe, Yutaro; Takada, Ryoji; Ikezawa, Kenji; Nawa, Takatoshi; Ashida, Reiko; Kimura, Toshihiro; Nagata, Shigenori; et al.
Abstract : ABSTRACT: A 61-year-old woman diagnosed with cervical cancer received systemic chemotherapy using paclitaxel and bevacizumab. Marked elevation of liver enzyme levels was observed. Ultrasonography and computed tomography showed wall thickening of the extrahepatic and intrahepatic bile ducts accompanied by stricture and dilatation. According to these, she was diagnosed as chemotherapy-induced sclerosing cholangitis (CISC), a form of secondary sclerosing cholangitis. Although CISC triggered by systemic chemotherapy is rare, CISC should be considered as a clinically important adverse event of chemotherapy because it causes rapid deterioration of liver function and necessitates interruption of chemotherapy.